ANALYSIS AND DETECTION POSSIBILITY OF THE PARTIAL DISCHARGES IN AIR INSULATED MEDIUM VOLTAGE SWITCHGEAR USING TRANSIENT EARTH VOLTAGE DETECTION - Buczko, Rafał; Sikora, Andrzej (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2016)
Modern switchgear increasingly use polymeric materials as insulation. Despite its numerous advantages they have limited resistance to partial discharge corrosion in some cases. In this paper noninvasive methods Transient Erath Voltage (TEV) measurement is proposed to detect various forms of partial discharges in medium voltage switchgear. These method allows for non-invasive diagnostic without switch of the switchgear. Measurement results confirm the effectiveness of the proposed approach.